Dalāʾil al-Nubuwwa Literature as Part of the Medieval Scholarly Discourse on Prophecy - Koertner, Mareike (Der Islam, 2018)
Abū Nuʿaym al-Iṣfahānī (d. 430/1038) and Abū Bakr Aḥmad al-Bayhaqī (d. 458/1066) are mostly considered early representatives of Dalāʾil al-Nubuwwa literature. As a consequence the genre itself has often been viewed as a subgenre of sīra literature, which bears stylistic, structural and methodological implications, and affects its reputation as popular hagiographic rather than scholarly literature. These implications may be partially valid for Dalāʾil al-Nubuwwa works in the time period of Abū Nuʿaym and al-Bayhaqī but not for earlier works that have not been systematically studied so far. In this article, I examine early authorship in Dalāʾil al-Nubūwa literature by identifying numerous works that significantly predate Abū Nuʿaym and al-Bayhaqī. I argue that this literature constituted a continuous tradition from the mid-2nd/8th century onward and that it originated in circles of well-respected ḥadīth scholars who upheld their field’s methodological processes of authentication. Around the second half of the 4th/10th century, authorship shifted toward less acclaimed scholars of ḥadīth or other intellectual fields. Along with this shift came stylistic, structural and methodological changes that have led to the common classification of these works as a subgenre of sīra literature.